Application of the multi-step homotopy analysis method to solve nonlinear differential algebraic equations - ZURIGAT, Mohammad (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
In this paper, a differential algebraic equations (DAE's) is studied and its approximate solution is presented using a multi-step homotopy analysis method (MHAM). The method is only a simple modification of the homotopy analysis method (HAM), in which it is treated as an algorithm in a sequence of small intervals (i.e. time step) for finding accurate approximate solutions to the corresponding systems. The solutions obtained are also presented graphically. Figurative comparisons between the MHAM and the exact solution reveal that this modified method is very effective and convenient. Mathematics Subject Classification (2010): 11Y35, 65L05.